2002
DOI: 10.1103/physreve.66.061707
|View full text |Cite|
|
Sign up to set email alerts
|

Shear-induced instabilities in layered liquids

Abstract: Motivated by the experimentally observed shear-induced destabilization and reorientation of smectic A like systems, we consider an extended formulation of smectic A hydrodynamics. We include both, the smectic layering (via the layer displacement u and the layer normalp) and the director n of the underlying nematic order in our macroscopic hydrodynamic description and allow both directions to differ in non equilibrium situations. In an homeotropically aligned sample the nematic director does couple to an applie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
67
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(73 citation statements)
references
References 47 publications
6
67
0
Order By: Relevance
“…2 since n and a are unit vectors, which is the form used in [1,2,29]. Although B 1 has been investigated theoretically, measurements for it are scarce in the literature.…”
Section: Dynamic Theorymentioning
confidence: 99%
See 4 more Smart Citations
“…2 since n and a are unit vectors, which is the form used in [1,2,29]. Although B 1 has been investigated theoretically, measurements for it are scarce in the literature.…”
Section: Dynamic Theorymentioning
confidence: 99%
“…Auernhammer et al [2]): the exact solutions can still be found when this approximation is not made but the results become unwieldy and tend to obscure the key roles of various material parameters. Notice also that, using (3.3), (3.2) can be rewritten as (3.5) ηu − uλ…”
Section: Geometrical Set-up and Governing Equationsmentioning
confidence: 99%
See 3 more Smart Citations